Comparison of femoral neck system vs. dynamic hip system blade for the treatment of femoral neck fracture in young patients: A retrospective study - Ge, Zilu; Xiong, Wei; Wang, Dong; Tang, Yunfeng; Fang, Qian; Wang, Limin; Zhang, Zhen; Lin, Wei; Wang, Guanglin (Frontiers in Surgery, 2023)
Background: Femoral neck fracture is a common fracture in orthopedic practice. This study aimed to compare the clinical outcomes between the femoral neck system and dynamic hip system blade for the treatment of femoral neck fracture in young patients. Methods: This retrospective study included 43 and 52 patients who underwent treatment for femoral neck fracture with the femoral neck system and dynamic hip system blade, respectively, between August 2019 and August 2020. Operative indexes, including operation duration, blood loss, incision length, postoperative complications (femoral neck shortening, non-union, screw pull-out, femoral head necrosis), and Harris scale scores were recorded and analyzed. Results: Compared to that with the dynamic hip system blade, the femoral neck system showed significantly less operation duration (femoral neck system vs dynamic hip system blade: 47.09±9.19 vs 52.90±9.64, P=0.004), less blood loss (48.53±10.69 vs 65.31±17.91, P<0.001), and shorter incision length (4.04±0.43 vs 4.93±0.53, P<0.001). Femoral neck shortening was significantly lower with the femoral neck system than with the dynamic hip system blade (3.93±2.40, n=39 vs 5.22±2.89, n=44, P=0.031). No statistical differences were observed between the two groups in nonunion, screw pull-out, and femoral head necrosis. In addition, the latest follow-up Harris scale score was significantly higher with the femoral neck system than with the dynamic hip system blade (92.3±4.5 vs 89. 9±4.9, P=0.015). Conclusion: The femoral neck system results in less trauma, less femoral neck shortening, and better hip joint function than the dynamic hip system blade for the treatment of femoral neck fracture in young patients.